Novel Node Localization Algorithm Based on Nonlinear Weighting Least Square for Wireless Sensor Networks. (8th November 2012) - Xiao, Fu; Wu, Mingtan; Huang, Haiping; Wang, Ruchuan; Wang, Sudan
Abstract : Positioning of the location information of wireless sensor network nodes is one of the key issues in wireless sensor network applications. The traditional node positioning method based on least-square algorithm heavily depends on the ranging accuracy, and therefore cannot guarantee high precision. This paper presents a new method for wireless sensor network node positioning based on nonlinear weighting least-square algorithm. Regarding ranging equation error-weighted sum as a whole, this method starts with the initial iteration point of stepwise refinement to explore the optimal solution and further reduces the positioning computational complexity by the simplification of the Taylor equation. Experimental results demonstrate that promising results have been achieved by using this method.